2019
DOI: 10.1177/000313481908500421
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Postoperative Complications after Acute Care Surgery: How Accurate is the ACS NSQIP Surgical Risk Calculator?

Abstract: The ACS NSQIP Surgical Risk Calculator (SRC) is an evidence-based clinical tool commonly used for evaluating postoperative risk. The goal of this study was to validate SRC-predicted complications by comparing them with observed outcomes in the acute care surgical setting. In this study, pre- and postoperative data from 1693 acute care surgeries (hernia repair, enterolysis, intestinal incision/excision and enterectomy, gastrectomy, debridement, colectomy, appendectomy, cholecystectomy, gastrorrhaphy, and incisi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 28 publications
1
18
0
Order By: Relevance
“…We should consider that discrimination and calibration results could substantially change between specific types of operations. For example, Golden et al [ 9 ] collected data from 1693 acute care procedures over a 5-year time period. They found that the calculator had a good discriminative power in predicting both serious and any complications rates after acute care surgeries (AUC 0.81 and 0.79, respectively) when considering the whole population as a single group.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We should consider that discrimination and calibration results could substantially change between specific types of operations. For example, Golden et al [ 9 ] collected data from 1693 acute care procedures over a 5-year time period. They found that the calculator had a good discriminative power in predicting both serious and any complications rates after acute care surgeries (AUC 0.81 and 0.79, respectively) when considering the whole population as a single group.…”
Section: Discussionmentioning
confidence: 99%
“…The authors considered the ACS-NSQIP SRC as reasonably accurate in terms of estimation of postoperative death and complication in the emergency setting, with readily obtainable objective data, which can be used in the early phases of decision making and care. Others confirmed that the ACS-NSQIP SRC accurately predicted complications after emergency procedures overall, but demonstrated a great variability in performance between procedure types [ 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ultimate outcome following surgical procedure is the result of interplay of so many factors which do not influence the risk calculator. 1,3,4 In the current procedural terminology (CPT) coding system which is a key input variable for the surgical procedure, it was experienced that multiple surgical procedures if contemplated in the same patient cannot be populated in the NSQIP software. Subramaniam et al in their study involving the use of ACS NSQIP calculator in head and neck oncologic conditions have eminently observed that prior radiotherapy to the area to be operated , microvascular anastomosis or chemo radiotherapy did influence the wound outcome which may cause flap necrosis , wound breakdown or wound infection altering the need of reoperation etc.…”
Section: Discussionmentioning
confidence: 99%
“…This tool is a guide to the surgeon in arriving at decision which is an inescapable component of the counselling and informed consent. 1,2,3 Several workers have published studies validating its use for a range of procedures. 4 This may be an important tool for surgical education in addition to "quality improvement" in surgical practice.…”
mentioning
confidence: 99%
“…For example, the American College of Surgeons National Surgical Quality Improvement Program surgical risk calculator 4 is reported to have generally good accuracy across a very wide range of procedures and specialties. However, other researchers 5,6 have found that this tool has low accuracy when tested for specific patients and procedures that differ from the overall sample in terms of the prevalence of inputs and outcomes.…”
Section: Is the Model Accurate For Subgroups?mentioning
confidence: 98%